Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Kang, Hao; Yu, Yongxiang; Liao, Meijie; Wang, Yingeng; Yang, Guanpin; Zhang, Zheng; Li, Bin; Rong, Xiaojun; Wang, Chunyuan (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes (gyrB, pyrH, recA, and atpA), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.